Strategi Pengembangan Sistem Informasi Akademik Dalam Upaya Peningkatan Mutu Pendidikan - Lestari, Triani Amrih; Mariah, Siti (Universitas Kristen Satya Wacana, 2018)
The purpose of this study is to formulate the strategy of academic information system development in an effort to improve the education quality through analysis of internal and external conditions in SMA Negeri 1 Petanahan Kebumen Central Java. Research type using mixed methods with SWOT (strengths, weaknesses, opportunities, threats) analysis approach. Data collection is done through interviews, documentation, observation, and questionnaires. The sampling technique using purposive sampling is 30 respondents. Data validity uses source and method triangulation, while data analysis techniques use IFAS and EFAS, as well as tools for formulating development strategies using SWOT Matrices. The results showed: the strength of academic information system SMA Negeri 1 Petanahan on infrastructure and academic data, while the weaknesses in resources and programs. Opportunities for academic information systems in the form of policies and strategic issues, while the threat is geographic. The research findings show that academic information system in SMA Negeri 1 Petanahan Kebumen in improving the education quality is in Growth cell: concentration through horizontal integration or stability strategy so it is appropriate to use SO strategy (strength-opportunity) that utilizes the infrastructure and academic data to meet the issue policy and strategic.